2019
DOI: 10.3906/tar-1803-99
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rootstocks on phytochemical properties of apricot fruit

Abstract: The phytochemical influence of rootstocks on the Hacıhaliloğlu apricot cultivar was examined in this study. Myrobolan 29-C, Myrobolan GF-31, Marianna 2624, Pixy, and Tokaloğlu rootstocks were used and organic acid, sugars, vitamin C, total antioxidant capacity, and phenolic compounds were identified. The highest phenolic compounds and antioxidant capacity were observed in Tokaloğlu rootstock. While Myrobolan GF-31 stood out in terms of organic acids and vitamin C, Pixy stood out in terms of sugar. The highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
(37 reference statements)
0
12
0
2
Order By: Relevance
“…Gallic acid was used as an external standard for the calibration curve, and the results were expressed as milligrams of gallic acid equivalent (mg GAE L -1 ) of fruit juice. The antioxidant activity of juices was determined using the ABTS + radical cation decolorization assay, as described by Gündoğdu (2019). Antioxidant activity was calculated using the ratio of the regression coefficient of the dose response curve and expressed in terms of millimoles of trolox equivalents per liter of fruit juice.…”
Section: Plant Materials and Experimental Treatmentsmentioning
confidence: 99%
“…Gallic acid was used as an external standard for the calibration curve, and the results were expressed as milligrams of gallic acid equivalent (mg GAE L -1 ) of fruit juice. The antioxidant activity of juices was determined using the ABTS + radical cation decolorization assay, as described by Gündoğdu (2019). Antioxidant activity was calculated using the ratio of the regression coefficient of the dose response curve and expressed in terms of millimoles of trolox equivalents per liter of fruit juice.…”
Section: Plant Materials and Experimental Treatmentsmentioning
confidence: 99%
“…The ratio of these compounds affects whether the fruits are sweet or sour. In addition, these compounds affect some enzyme activities and react with other biochemical compounds and take part in many physiological events in fruits (Aytül et al, 2019;Gündoğdu, 2019). Aonla is regarded as sacred by Hindus and has great mythological significance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they play an important role in human health and life. The fruits contain a lot of different phenolics and organic acids which their levels vary depending on the cultivars (Dragovic-Uzelac et al, 2007;Eyduran et al, 2015;Gündoğdu, 2019;Ozturka et al, 2019). Ersoy et al (2018) reported that fruits of red currants are rich in catechin, rutin, gallic acid from phenolic compounds, and citric acid from organic acids.…”
Section: Introductionmentioning
confidence: 99%